5 questions on Agile - Ruma, Laurel (O'Reilly, 2018)
"In this interview, O'Reilly Media Content Director Laurel Ruma talks to Lauri Apple about how Zalando applies Agile practices. Lauri is responsible for developing Zalando's open-source culture and promoting its projects industry-wide. She's also leading Zalando's InnerSource initiative to drive the open-source collaboration model internally, and project-managing a development team."--Resource description page